If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3876 = x + -68(57) Multiply -68 * 57 3876 = x + -3876 Reorder the terms: 3876 = -3876 + x Solving 3876 = -3876 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3876 + -1x = -3876 + x + -1x Combine like terms: x + -1x = 0 3876 + -1x = -3876 + 0 3876 + -1x = -3876 Add '-3876' to each side of the equation. 3876 + -3876 + -1x = -3876 + -3876 Combine like terms: 3876 + -3876 = 0 0 + -1x = -3876 + -3876 -1x = -3876 + -3876 Combine like terms: -3876 + -3876 = -7752 -1x = -7752 Divide each side by '-1'. x = 7752 Simplifying x = 7752
| 10(x-11)=0 | | 12+4(6-5x)=26-15x | | 18=60-y | | 3(2+4)-(3-1)= | | 0.82+2.5(0.5)= | | (90/30)-12=60-y | | 4s-5t=2 | | Log[4](x-7)-log[4](x-4)=2 | | 2(4t-6)=17t+8 | | 84-(6x+3)=6(x+7)+x | | -(-7y)-y=-12 | | 6x=176-5x | | 6x-3/8=141/8 | | (90/30)-12=(12x5)-y | | 2(6x+24)=2(7+14) | | 14=2/3(9y-5) | | 1x-3=32 | | (90/30)-12=(12•5)-y | | 19x-4(5x-7)=40 | | 13x-(4x-9)=81 | | 115(77-48)= | | sqrt(x-2)+4=x | | 7+3(y-7)=15 | | 3-(x-2)=17 | | 3(2x+3)=5x | | 92(23+36)= | | x-68/57=68/129.2 | | 2-2cos^2x-5sinx=-2 | | 2.2(x+4)=2(x+8) | | (5/12)=(18/(3x-3)) | | an=-6+14n | | ln(e^21x)=7 |